PENTINGNYA LITERASI KEUANGAN UNTUK KELOMPOK WANITA TANI MEKARSARI DALAM MENINGKATKAN KEMANDIRIAN EKONOMI - Syamsu Nujum; Tenriwaru Tenriwaru; Serlin Serang; Aryati Aryati (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2026)
This Community Service Program (PKM) aims to enhance the financial literacy of the Mekar Sari Women Farmers Group in order to strengthen the members’ economic independence. The lack of understanding in managing household and farming finances has been identified as one of the main obstacles to improving family economic development. The program was implemented through a participatory approach, including socialization, training, mentoring, and evaluation of participants’ financial management skills. The training materials covered financial planning, simple cash flow recording, savings management, and strategies for productive use of business capital. The results showed a significant improvement in participants’ understanding and skills in budgeting, transaction recording, and managing business income independently. Furthermore, the program fostered greater awareness of the importance of long-term financial planning for family economic sustainability. This PKM activity has made a tangible contribution to enhancing financial literacy and economic independence among the Mekar Sari Women Farmers Group.